Efficacious and safe management of thick scales, redness and flaky scalp condition using a specific shampoo containing urea, glycolic acid, salicylic acid, icthyol pale and laureth 9 - Bianca Maria Piraccini; Nicolò Brandi; Aurora Alessandrini; Francesca Bruni; Michela Starace (Cogent Medicine, 2018)
Dandruff is a common condition, generally due to seborrheic dermatitis (SD) and occasionally to scalp psoriasis (SP), which is characterized by accumulation of scales, oily, red and flaky scalp, often accompanied by itch. The aim of our study was to evaluate the cleansing efficacy and tolerability of a new shampoo (Psorisdin Shampoo®) containing urea, glycolic acid, salicylic acid, ichthyol pale and laureth 9 compared to a nonspecific shampoo. A total of 10 subjects (4 males and 6 females, 18–60 years) with mild–moderate scalp inflammation with redness, itching and flaking, due to SP and/or SD, were included in this open clinical study. The treatment efficacy was assessed by comparison of global photography and trichoscopy pictures, evaluating the presence of scales and erythema on the scalp, the number and morphology of capillaries and verifying disease evolution, severity of symptoms and presence of scalp irritation/itch. The use of this medicated shampoo resulted in an important improvement of patient’s scalp and hair clinical appearance and was well tolerated, with disappearance of scalp irritation and itching in almost all patients, showing higher cleansing and soothing property than a nonspecific shampoo. The effect of the tested shampoo was maintained over time, even after 5 days since the last wash.